(untitled) (Global Journal of Human-Social Science, 2024)
In this article the author presents the characteristics and conceptual criteria that should identify a femicide according to the original conception of Femicide -or Feminicide- of the English term Femicide first developed by the feminist Diana Russell First the author contrasts the original conceptualization of femicide and the technical definition proposed by the legislator in the Bolivian Penal Code on the classification of the crime of femicide and then makes a critical analysis of it Second he states that the concept of femicide -or feminicide- alludes to specific criteria for example the misogynist murder of a woman because of her gender simply because she is a woman Third the author analyzes the mental state test and its conceptualization Fourthly he analyzes the systems of valuation of evidence Likewise he analyzes the system of sound criticism as a corrective criterion of justification of the judicial decision Finally he analyzes the evaluation of evidence and the evidential reasoning to which the independent and impartial judge or court must adjust